Nexus Between Citizen Participation and Performance of County Assemblies in Kenya - Kaberia, Isaac Joseph; Senaji, Thomas; Rintari, Nancy (International Journal of Professional Practice, 2021)
Worldwide, public participation in decision making has been advocated as being essential for the effectiveness of public organizations. County assemblies in Kenya are legally required to implement laws guiding public participation in decision making. Though citizen participation in decision making is essential for implementation of the mandate of county assembles (oversight, representation, and legislation), the extent of its relationship with performance of county assemblies in Kenya is not clear. Whilst there is a strong impetus towards conducting public participation by county assemblies in Kenya, there is a gap between the provisions in the legal framework and actual practice on the ground leading to poor public participation which has an effect on the performance of county assemblies in Kenya. This study examined the nexus between citizen participation in decision making and performance of County assemblies in Kenya. Correlation analysis was used to assess the strength and direction of the relationship between citizen participation in decision making and effectiveness in performance of county assemblies in Kenya. The study found a strong correlation between citizen participation and county assembly efficiency (r = 0.448, p). This study filled the gap that existed mainly on involving citizens in decision making. To improve performance of county assemblies, there is need to involve the citizens, to foster collaboration among and within counties, and to network with stakeholders.